Selected pharmaceuticals entering an estuary: Concentrations, temporal trends, partitioning, and fluxes. (30th June 2016) - Cantwell, Mark G.; Katz, David R.; Sullivan, Julia C.; Ho, Kay; Burgess, Robert M.; Cashman, Michaela
Abstract: In many coastal watersheds and ecosystems, rivers discharging to estuaries receive waters from domestic wastewater‐treatment plants resulting in the release and distribution of pharmaceuticals to the marine environment. In the present study, 15 active pharmaceutical ingredients were measured regularly over 1 yr in the dissolved and particulate phases as they entered Narragansett Bay from the Pawtuxet River in Cranston (Rhode Island, USA). Of the active pharmaceutical ingredients measured, 14 were consistently present in the dissolved phase, with concentrations ranging from below detection to >310 ng/L, whereas 8 were present in the particulate phase (0.2–18 ng/g). Partition coefficients ( K d s and K OC s) were determined, and organic carbon normalization reduced variability associated with K d s for the active pharmaceutical ingredients evaluated. Flux estimates based on river flow were calculated for both dissolved and particulate‐phase active pharmaceutical ingredients, with particulate fluxes being low (1–12 g/yr) and dissolved fluxes of active pharmaceutical ingredients being 155 g/yr to 11 600 g/yr. Results indicate that the pharmaceuticals measured in the present study reside primarily in the dissolved phase and thus are likely bioavailable on entering the estuarine waters of Narragansett Bay. This long‐term temporal study provides important information on seasonal and annual dynamics of pharmaceuticals in an urban estuarine watershed. Environ Toxicol Chem 2016;35:2665–2673. Published 2016 Wiley Periodicals Inc. on behalf of SETAC. This article is a US Government work and, as such, is in the public domain in the United States of America.